Subunits of purified calcium channels: a 212-kDa form of alpha 1 and partial amino acid sequence of a phosphorylation site of an independent beta subunit. - De Jongh, K S (1989)
Antibodies prepared against peptides CP2, CP4, and CP5, which occur within the first 1522 amino acid residues of the alpha 1 subunit of dihydropyridine-sensitive skeletal muscle calcium channels, specifically recognized a 175-kDa form of the alpha 1 subunit in immunoblots and immunoprecipitation experiments. In contrast, antibodies prepared against peptide CP1, which represents the C-terminal 18 amino acid residues predicted by cloning and sequence analysis of the alpha 1 subunit, recognized a minor, previously undescribed 212-kDa protein, which is the size predicted for the full length of the alpha 1 subunit from cDNA cloning [Tanabe, T., Takeshima, H., Mikami, A., Flockerzi, V., Takahashi, H., Kangawa, K., Kojima, M., Matsuo, H., Hirose, T. & Numa, S. (1987) Nature (London) 328, 313-318]. Both the 175-kDa and 212-kDa forms were phosphorylated by cAMP-dependent protein kinase and both were present in isolated transverse tubule membranes. The 175-kDa form may arise from posttranslational proteolytic cleavage of the C terminus of the 212-kDa form of the alpha 1 subunit predicted by cDNA cloning and sequence analysis. Partial amino acid sequencing of the 54-kDa beta subunit of the calcium channel indicated this protein was not derived from the proteolytically cleaved C terminus of the alpha 1 subunit. This analysis identified a threonine residue in the sequence (Lys/Arg)-Arg-Pro-Thr-Pro of the beta subunit that was phosphorylated by cAMP-dependent protein kinase. Phosphorylation of this residue in the beta subunit may play a role in modulation of calcium channel function. Separate functional roles of the 175-kDa form of the alpha 1 subunit in excitation-contraction coupling and of the 212-kDa form in ion conductance are proposed.